Subduction system and flat slab beneath the Eastern Cordillera of Colombia. (5th January 2016) - Chiarabba, Claudio; De Gori, Pasquale; Faccenna, Claudio; Speranza, Fabio; Seccia, Danilo; Dionicio, Viviana; Prieto, Germán A.
Abstract: Seismicity at the northern terminus of the Nazca subduction is diffused over a wide area containing the puzzling seismic feature known as the Bucaramanga nest. We relocate about 5000 earthquakes recorded by the Colombian national seismic network and produce the first 3‐D velocity model of the area to define the geometry of the lithosphere subducting below the Colombian Andes. We found lateral velocity heterogeneities and an abrupt offset of the Wadati‐Benioff zone at 5°N indicating that the Nazca plate is segmented by an E‐W slab tear, that separates a steeper Nazca segment to the south from a flat subduction to the north. The flat Nazca slab extends eastward for about 400 km, before dip increases to ∼50° beneath the Eastern Cordillera, where it yields the Bucaramanga nest. We explain this puzzling locus of intermediate‐depth seismicity located beneath the Eastern Cordillera of Colombia as due to a massive dehydration and eclogitization of a thickened oceanic crust. We relate the flat subducting geometry to the entrance at the trench at ca. 10 Ma of a thick ‐ buoyant oceanic crust, likely a volcanic ridge, producing a high coupling with the overriding plate. Sub‐horizontal plate subduction is consistent with the abrupt disappearance of volcanism in the Andes of South America at latitudes > 5°N. Key Points: This is the first high resolution image of seismicity and tomography of the Colombian Andes Deep seismicity and velocity anomalies define tears and flattening of the Nazca slab We explain the Bucaramanga seismicity nest with massive dehydration of the subducting Nazca plate